Fault Tolerant Control Algorithm of Hexarotor UAV - Songming Jiao; Haiyue Gao; Xiaokun Zheng; Dengpan Liu (Journal of Robotics)
As the best representative of the current cutting-edge technology, unmanned aerial vehicle (UAV) is widely used in various fields such as electric power inspection, agriculture, forestry and plant protection, fire rescue, and film and television shooting. With the rapid development of UAV, the safety work of UAV has become more important. In order to improve the safety of hexarotor UAV during flight, a fault-tolerant control scheme independent of basic control law and control distribution is designed in this paper. Firstly, the linear active disturbance rejection control (LADRC) was used as the basic control law for attitude control of hexarotor UAV. Secondly, in the case of actuator failure of hexarotor UAV, a fault observer was used to estimate fault information accurately. Then, on this basis, the control distribution matrix was adjusted to reduce the use of the faulty motor, and the purpose of fault-tolerant control was achieved. Finally, simulation experiments and actual flight experiments were carried out to verify the effectiveness of the proposed scheme. Experimental results show that the proposed scheme can improve the robustness of the control system and the flight safety of UAV.